NARRATIVE REVIEW : METODE EKSTRAKSI GANODERMA LUCIDUM DAN EFEKTIVITASNYA - Meinanda Grabilia; Diana Laila Rahmatillah; Kashif Khan (Fakultas Farmasi Universitas 17 Agustus 1945 Jakarta, 2026)
Ganoderma lucidum is one of the medicinal mushrooms that has been extensively researched due to its bioactive compounds, particularly polysaccharides, triterpenoids, and phenolic compounds, which exhibit a wide range of pharmacological activities. Various extraction methods have been developed to optimally obtain these bioactive components, ranging from conventional techniques like hot water and ethanol extraction to modern methods such as ultrasonic extraction, microwave-assisted extraction, and enzyme-based combinations. This review article aims to identify the types of extraction methods used on G. lucidum and evaluate their effectiveness based on the resulting active compound composition and biological activity. The review results indicate that differences in solvents, temperature, duration, and processing techniques significantly affect the yield and stability of bioactive components. The extracted compounds have been proven to possess antioxidant, antimicrobial, hepatoprotective, immunomodulatory, and antitumor activities, although their effectiveness varies across studies due to the lack of standardisation in the extraction process. This review emphasises the importance of selecting the appropriate extraction method based on the target compounds, as well as the need for further research to standardise the process and quantitatively compare the effectiveness of the methods. Thus, the therapeutic potential of G. lucidum can be utilised more optimally in the development of herbal-based health and pharmaceutical products.Keywords: Ganoderma lucidum, extraction method, bioactive, effectiveness